Association of Neuropathic Pain Symptoms with Sensitization Related Symptomatology in Women with Fibromyalgia - Edurne Úbeda-D’Ocasar; Juan Antonio Valera-Calero; Gracia María Gallego-Sendarrubias; César Fernández-de-las-Peñas; José Luis Arias-Buría; Matilde Morales-Cabezas; Lars Arendt-Nielsen; Margarita Cigarán-Méndez (Biomedicines, 2022)
We aimed to analyze potential correlations between S-LANSS and PainDETECT with proxies for pain sensitization, e.g., the Central Sensitization Inventory (CSI) and pressure pain hyperalgesia (construct validity), pain-related or psychological variables (concurrent validity) in women with fibromyalgia (FMS). One-hundred-and-twenty-six females with FMS completed demographic, pain-related variables, psychological, and sensitization outcomes as well as the S-LANSS and the PainDETECT questionnaires. S-LANSS was positively associated with BMI (r = 0.206), pain intensity (r = 0.206 to 0.298) and CSI score (r = 0.336) and negatively associated with all PPTs (r = −0.180 to −0.336). PainDETECT was negatively associated with age (r = −0.272) and all PPTs (r = −0.226 to −0.378) and positively correlated with pain intensity (r = 0.258 to 0.439), CSI (r = 0.538), anxiety (r = 0.246) and depression (r = 0.258). 51.4% of the S-LANSS was explained by PainDETECT (45.3%), posterior iliac PPT (0.2%) and mastoid PPT (5.9%), whereas the 56.4% of PainDETECT was explained by S-LANSS (43.4%), CSI (10.4%), and pain intensity (2.6%). This study found good convergent association between S-LANSS and PainDETECT in women with FMS. Additionally, S-LANSS was associated with PPTs whereas PainDETECT was associated with pain intensity and CSI, suggesting that both questionnaires assess different spectrums of the neuropathic and pain sensitization components of a condition and hence provide synergistic information.